HUBUNGAN ANTARA BERAT LAHIR DENGAN REFLUKS GASTROESOFAGUS PADA BAYI USIA 0–1 TAHUN - Hamzah Haryo Prakoso; Evi Rokhayati; Dwi Hidayah, (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Low birth weight babies are population at risk for gastroesophageal reflux and its complications due to physiologic immaturity of digestive system. However, the pathomechanism remains unclear. There is no similar study conducted in Surakarta City and still lack of studies on 0-1 year infants. The aim of this study is to evaluate Gastroesophageal reflux risk in low birth weight infants age 0–1 year. Method: Case control study on infants aged 0–1 year in Ngoresan Public Health Center, Surakarta. Samples were obtained by purposive sampling method in April–May 2021 with a questionnaire on infant characteristics and the Infant-Gastroesophageal Reflux Questionnaire as research instruments. Results: There were 60 samples divided into case and control groups with a 1:1 ratio. There was no significant relationship between birth weight and gastroesophageal reflux (p = 0.612). Discussion: Research conducted in Semarang and Italy declared no correlation between birth weight and gastroesophageal reflux. The relationship is more visible if infants have a birth weight <1,500 grams and a history of the disease such as bronchopulmonary dysplasia or chronic lung disease. Conclusion: There is no relationship between birth weight and gastroesophageal reflux in infants aged 0–1 years